Design and Fabrication of Standing Wave Thermoacoustic Refrigerator for Demonstration Purpose - Yapri, Kevin
Thermoacoustic refrigerator is a kind of machine that utilizes acoustic phenomenon to create a cooling effect, which is obtained from thermodynamic interaction between oscillating gas particles with solid walls, thus creating a temperature gradient. Thermoacoustic refrigerator has an advantage over vapor compression refrigerator, which it can run without electricity. Even so, almost all ITB student have never heard about thermoacoustic refrigeration. Hence, to introduce this technology to them, a standing wave thermoacoustic refrigerator for demonstration purpose was designed, made, tested, and analyzed. The refrigerator made has an electronic system, stack, and resonator tube. The electronic system consists of user interface, microcontroller, temperature measurement system, audio source, amplifier, and speaker. Air is used as working fluid because it is easy to obtain and its ODP (Ozone Depletion Potential) and GWP (Global Warming Potential) are zero. This educational aid device is easy to use because there are only four buttons to interact with and to give commands to the microcontroller. This device is also easily observed because it use Pyrex glass as its resonator tube, so the inside is clearly visible, and the temperature of both ends of stack can be easily seen on LCD screen. The experiment was done to find out the frequency and location of the stack which produces the lowest temperature and highest temperature difference. The results shown that frequency of 150 Hz and the stack’s location being 60 mm from the closed end gave the best cooling effects. The cold side and hot side’s temperature obtained from this combination of position and frequency were 23.2C and 43.7C, respectively.